Mosque Functions as Islamic Education Centers in Overcoming Community Crisis - Gusni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
This paper relates to the function of mosques as centers of Islamic education in overcoming the moral crisis in society. In connection with the title, the author explains the function of mosques in overcoming society's moral crisis. To answer this problem, the author uses library research, where he examines several books that are related to the problem being discussed. In this case, the author uses the direct quotation technique, that is, the author quotes a book or article without changing the editorial at all. And the indirect quotation technique, namely, the author quotes the book by adding the editorial, but the meaning and purpose remain the same. In this research, the results showed that the existence of a mosque in the midst of society needs to be considered both in terms of development and in terms of prosperity, with various religious activities in it such as congregational prayers, ta'lim assembly meetings, and various mosque youth guidance, especially during the holy month of Ramadan. various activities such as the Nuzulul Qur'an, a pious children's festival, and guidance for reading and writing the Qur'an. So that the function of the mosque can bring a wind of change for the better and spread peace and the nobility of morals in society.